Edema in oral rehydration - Sugijanto Sugijanto; Nassir Abbas (Indonesian Pediatric Society, 1981)
During 7 monts from February through September 1978, 160 cases of moderate dehydration due to diarrheal diseases had been admitted to the Department of Child Health of the General Hospital Ujung Pandang.All of them received ORS orally ad libitum or by gastric drips. Seven children (5 females and 2 males) showed periorbital with or without pretibial edema, aged 2 - 16 months with a bodyweight of 3.4- 9.5 kg.Three out of seven children had good nutritional status, 3 others were undernourished and 1 had severe malnutrition.All children got ORS ranging between 500-4400 mL. Edema disappeared within 9.5-48 hours after withdrawal of ORS.The relationship between edema and age, sex, nutritional status and total amount of ORS/Na+ received was still not understood but edema appeared more frequently in cases receiving ORS/Na+ excessively.